METODE PEMANASAN DAN SONIKASI MENGHASILKAN NANOLIPOSOM DARI FOSFOLIPID LESITIN KEDELAI (SOY LECITHIN) - Rini Dwiastuti; Sri Noegrohati; Enade Perdana Istyastono; Marchaban Marchaban (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2016)
Liposomes in topical drug delivery preparation is developed because having a good penetration through the skin. The lecithin which is often used in liposome formulations is soy lecithin. Heating and sonication methods can be done to reduce the size of the particles. This study aims to produce nanoliposom dosage formulations of soy lecithin phospholipids by using a combination of heating and sonication methods to generate liposomes with size 150nm . The methods of nanoliposomes preparation in this study using a combination of heating 60?C and sonication methods for about 30 minutes in the manufacturing process . The results showed that the preparation of nanoliposomes formulation from soy lecithin can be done by using a combination of heating 60?C and sonication methods for about 30 minutes.